Digital Skills Unlocking the Information Society - Dijk, Jan A. G. M. van.; Deursen, Alexander J. A. M. van.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
The first book to systematically discuss the skills and literacies needed to use digital media, particularly the Internet, van Dijk and van Deursen's clear and accessible work distinguishes digital skills, analyzes their roles and prevalence, and offers solutions from individual, educational, sociological, and policy perspectives.
Keywords: Science; Science; Science, general